The extract of Jeruju plant for anti-inflammatory: A literature review using nursing perspective - Nia Afifatul Ulya; Heni Setyowati Esti Rahayu; Prasojo Pribadi (Journal of Holistic Nursing Science, 2022)
Jeruju plant has some benefits in reducing symptoms of a particular disease. However, there is little discussion about plants in nursing. Therefore, the literature review aims to identify the effectiveness of Jeruju plant extract as an anti-inflammatory. The method used is a literature review integrating electronic databases such as Google Scholar and ScienceDirect. The keywords used in Indonesian are "Acanthus ilicifolius as anti-inflammatory," and the keywords in English are "Acanthus ilicifolius AS anti-inflammatory." The Jeruju plant (Acanthus ilicifolius) contains flavonoids acting as an anti-inflammatory. Flavanoids help to reduce the inflammation in the disease. The clinical nurse may use the finding of this review for health promotion for the patient with chronic illness. Keywords: Complementary therapy; community nursing; elderly care; quality of life; nursing intervention